CONCEPTUAL EQUIVALENCE IN LITERARY TRANSLATION: AN ANALYSIS BASED ON THE ANTHROPOCENTRIC APPROACH - Bakhriddinova Madina Shavkatovna (International Journal of Literature and Language Studies, 2026)
Abstract: Conceptual equivalence remains one of the most challenging issues in literary translation due to the interaction of linguistic, cognitive, cultural, and aesthetic factors. Within the anthropocentric paradigm, translation is viewed as a human-centered process in which translators actively interpret and reconstruct meanings according to their cognitive experience and cultural competence. The present study investigates the problem of conceptual equivalence in literary translation from an anthropocentric perspective. Employing a mixed-methods research design, the study analyzes conceptual units extracted from English and Uzbek literary texts and their translated versions. Quantitative analysis identifies the frequency of translation strategies used to achieve conceptual equivalence, while qualitative analysis explores cognitive mechanisms underlying translators’ decisions. The findings indicate that conceptual equivalence is achieved primarily through cultural adaptation and explicitation rather than direct lexical correspondence. The research contributes to contemporary translation studies by highlighting the role of cognition, culture, and human perception in literary translation.